Highly specific host-pathogen interactions influence Metarhizium brunneum blastospore virulence against Culex quinquefasciatus larvae. Issue 1 (31st December 2018) - Alkhaibari, Abeer M.; Lord, Alex M.; Maffeis, Thierry; Bull, James C.; Olivares, Fabio L.; Samuels, Richard I.; Butt, Tariq M.
ABSTRACT: Entomopathogenic fungi are potential biological control agents of mosquitoes. Our group observed that not all mosquitoes were equally susceptible to fungal infection and observed significant differences in virulence of different spore types. Conidiospores and blastospores were tested against Culex quinquefasciatus larvae. Blastospores are normally considered more virulent than conidia as they form germ tubes and penetrate the host integument more rapidly than conidia. However, when tested against Cx. quinquefasciatus, blastospores were less virulent than conidia. This host-fungus interaction was studied by optical, electron and atomic force microscopy (AFM). Furthermore, host immune responses and specific gene expression were investigated. Metarhizium brunneum (formerly M. anisopliae ) ARSEF 4556 blastospores did not readily adhere to Culex larval integument and the main route of infection was through the gut. Adhesion forces between blastospores and Culex cuticle were significantly lower than for other insects. Larvae challenged with blastospores showed enhanced immune responses, with increased levels of phenoloxidase, glutathione-S-transferase, esterase, superoxide dismutase and lipid peroxidase activity. Interestingly, M. brunneum pathogenicity/stress-related genes were all down-regulated in blastospores exposed to Culex . Conversely, when conidia were exposed to Culex, the pathogenicity genes involved in adhesion or cuticle degradation were up-regulated. Delayed host mortality following blastospore infection of Culex was probably due to lower adhesion rates of blastospores to the cuticle and enhanced host immune responses deployed to counter infection. The results here show that subtle differences in host-pathogen interactions can be responsible for significant changes in virulence when comparing mosquito species, having important consequences for biological control strategies and the understanding of pathogenicity processes.